Al-Farabi's Concept of Political Welfare - Atsir Ahmad Salman; Muhammad Fajar Pramono; Amir Reza Kusuma; Iqbal Maulana Alfiansyah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
The State is formed because of the human need to live together, so it can be concluded that the existence of the State is a necessity in life human. Al-Farabi speaks with physical and spiritual happiness, Sa'adah maddiyah wa ma'nawiyyah, this will not be obtained by people unless they live in a community in an ideal state, al-Madinah al-fadilah. Al-Farabi's political theory of the State boils down to the regulation of the existence of god and devotion to him (theocentric). In contrast to Greek political and statehood theories, al-Farabi later stated that the purpose of statehood was obtain happiness and justice. Al-sa‟adah means happiness, contains the understanding of things that are good to us that are obtained a person is a gift from Allah SWT alone.